Peran dan Tantangan Sistem Keadilan Pemilu dalam Pelaksanaan Pilkada - Ahmad Zulfiqar; Muhtadi; Satria Prayoga (Jurnal Hukum Lex Generalis, 2025)
The Regional Elections are a democratic process of electing regional heads. In its implementation, the regional elections must reflect the principles of electoral justice. However, the experience of the regional elections that have been passed does not reflect the fairness of the election so that the principles of direct, public, free, secret, honesty, and fair do not run well. The importance of this electoral justice system is to prevent fraud, money politics, and maintain voting rights. Thus, the implementation of the Regional Elections must be oriented towards justice and guarantee the right to vote and be elected. It is very important to deeply understand the role of electoral justice in building the election system so that the democratic process that runs in the regions can be carried out in a fair, transparent, and upholding the sovereignty of the people.